Gitar Dalam Karya Digital Painting - Heru Syahputra; Syafei Syafei (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This work aims to visualize the problems of adolescents experienced by the author through the image of a guitar which is used as a metaphor in digital painting works. The hope of this work is to improve the messages contained, to be able to inspire and provide support to teenagers who find it difficult to deal with problems. With this work, the author seeks to raise awareness of the importance of mutual understanding and provide space to talk about sensitive issues in the youth environment. The method of creating this work follows five stages, namely: preparation, in which the author makes observations and explorations to find inspiration. Then, at the elaboration stage, relevant references are collected and searched. The third stage, synthesis, involves applying the ideas and main ideas that have been generated. Furthermore, at the concept realization stage, the final work is made based on the previously designed concept. Finally, at the completion stage, the work is exhibited and a report is created covering the entire process from start to finish. In creating works, the author uses the Krita application as a technique in making digital painting works. Each work features a guitar object consisting of 10 works with the titles, "Break up", "Abandoned", "Stuck", "Confused", Depression", "Social Media", "Frenzy", Academic", "Bully", and “trapped”